Relationship among organizational factors, knowledge management processes, organizational innovation, and organizational performance in Iranian public banks - Naghavi, Mojtaba (2012)
The purpose of this study was to examine the relationship among major variables that include organizational factors (OFs), Knowledge Management processes (KMP),organizational innovation (INO), and organizational performance (PER) in the public banks in Iran. In addition, the roles of KMP and INO as mediators were investigated. Seven research questions and 28 hypotheses were examined. The unit of analysis was the supervisory department of the Iranian public banks’ branches. A questionnaire was used as the main instrument in gathering data, and a total of 229 respondents were involved in the survey. As an analytical method, Structural Equation Modeling (SEM) was selected using Amos 16.0 version. Result of the SEM analysis revealed that; a) Variables leadership, collaboration,centralization, training, and IT support of the OFs have significant relationships with KMP. b) Variables leadership, incentives, formalization and IT support of the OFs have significant relationships with INO. c) There is a significant positive relationship between KMP and PER. d) There is a significant positive relationship between KMP and INO. e) There is a significant positive relationship between INO and PER. f) KMP partially mediates the relationship between variables leadership and IT support of the OFs with INO. g) INO partially mediates the relationship between KMP and PER. The findings of the structural model analyses also determine that 61% of the variance in the KMP is explained by the joint influences of the OFs predictors, 49% of the variance in the INO is accounted by the joint influences of the predictors of OFs and KMP. In addition, 73% of the variance in the PER is accounted by the joint influences of the predictors of OFs, KMP and INO. The result of overall structural model showed that the IT support variable of the OFs had the highest contribution toward the prediction of organizational performance and this is followed by the leadership and collaboration variables respectively.